185 Stage 1B2 invasive cervical cancer diagnosed at 20 weeks gestation: neoadjuvant chemotherapy followed by caesarean radical hysterectomy at term and chemoradiation: report of a case. (18th September 2019) - Konney, T; Johnston, C; Amo-Antwi, K; Appiah-Kubi, A; Tawiah, A; Antwi-Kusi, A; Osei-Bonsu, E; Odoi, AT
Abstract : Objectives: The diagnosis and treatment of cervical cancer during pregnancy is a challenge that requires a multi-disciplinary approach. The management depends on the gestational age at diagnosis, the stage of disease, the woman's desire to continue the pregnancy and desire to preserve fertility. Neoadjuvant chemotherapy (NACT) is a treatment option for women diagnosed before 24 weeks gestation who wish to continue the pregnancy. Our objective was to present the first such case in West Africa. Methods: We present a 40-year old G3P2 with stage IB2 poorly differentiated squamous cell carcinoma of the cervix diagnosed at 20-weeks' gestation. She received 3 cycles of NACT with Cisplatin 75 mg/m 2 and Paclitaxel 135 mg/m 2 followed by caesarean radical hysterectomy and pelvic lymphadenectomy at 37 weeks and 4 days. We reviewed the relevant literature for similar cases. Results: The tumour size shrank by 50% by the third cycle and bleeding ceased by the start of the second cycle. The baby weighed 2.2kg with good Apgar scores. Histopathology showed resection margins to be free of disease, positive for lymphovascular space invasion, tumour size of 4cm and residual tumour in bilateral pelvic lymph nodes. The patient completed whole pelvic radiation and brachytherapy. Both mother and infant are doing well at 10 months post-treatment and are in surveillance. Conclusions: We demonstrate that NACT followed by caesarean radical hysterectomy is a safe option to delay delivery of the baby in the management of locally invasive cervical cancer first diagnosed in pregnancy. NACT led to cessation of vaginal bleeding and tumour shrinkage.